Conclusion - Alginahi, Yasser M.; Kabir, M. Nomani (The Institution of Engineering and Technology (IET), 2019)
The book contains theoretical and practical knowledge of state-of-the-art authentication technologies and their applications in big data, IoT, and cloud computing with this technologically connected world. The first six chapters of the book provide the fundamental details of the authentication technologies.The objective of Chapters 7 to 11 is to develop fast and secure algorithms for resource-constrained IoT and cloud computing, while the aim of Chapter 12 is to protect the data by laws and policies. All these chapters include research challenges and future research directions with the evolution of technologies.